Evaluating stored platelet shape change using imaging flow cytometry. (1st January 2023) - Özpolat, Tahsin; Yakovenko, Olga; Stratiievska, Anastasiia; Bailey, S. Lawrence; Miles, Jeffrey; Usaneerungrueng, Chomkan; Byrne, Daire; Wu, Xiaoping; Stolla, Moritz
Abstract: Platelets are routinely stored at room temperature for 5–7 days before transfusion. Stored platelet quality is traditionally assessed by Kunicki's morphology score. This method requires extensive training, experience, and is highly subjective. Moreover, the number of laboratories familiar with this technique is decreasing. Cold storage of platelets has recently regained interest because of potential advantages such as reduced bacterial growth and preserved function. However, platelets exposed to cold temperatures change uniformly from a discoid to a spherical shape, reducing the morphology score outcomes to spheroid versus discoid during cooling. We developed a simpler, unbiased screening tool to measure temperature-induced platelet shape change using imaging flow cytometry. When reduced to two dimensions, spheres appear circular, while discs are detected on a spectrum from fusiform to circular. We defined circular events as having a transverse axis of >0.8 of the longitudinal axis and fusiform events ≤0.8 of the longitudinal axis. Using this assay, mouse and human platelets show a temperature and time-dependent, two-dimensional shape change from fusiform to circular, consistent with their three-dimensional change from discs to spheres. The method we describe here is a valuable tool for detecting shape change differences in response to agonists or temperature and will help screening for therapeutic measures to mitigate the cold-induced storage lesion. Plain Language Summary: What is the context? Platelets for transfusion are currently stored for 5–7 days at room temperature, increasing the risk for bacterial growth Cold storage reduces the risk for bacterial growth but reduces circulation time Stored platelet quality can be assessed by the light microscopy-based Morphology Score, first described in the 1970s Downsides of the Morphology Score include subjectivity, extensive training, and reduced availability in platelet laboratories. What is new? In this study, we provide data showing that the Morphology score is reduced to a binary spheres versus discs response in cold-exposed platelets We developed an imaging flow cytometry-based approach to quantify platelets' response to cold based on the two-dimensional projection of the three-dimensional shapes, i.e., fusiform (discoid) versus circular (discoid and spherical) We provide validation of this approach in mouse and human platelets What is the impact? This study provides an easy and unbiased tool for laboratories working on circumventing the cold-induced storage lesion or documenting spherical shape change in general